2015
DOI: 10.1007/978-3-319-23219-5_10
|View full text |Cite
|
Sign up to set email alerts
|

Conflict Ordering Search for Scheduling Problems

Abstract: Abstract. We introduce a new generic scheme to guide backtrack search, called Conflict Ordering Search (COS), that reorders variables on the basis of conflicts that happen during search. Similarly to generalized Last Conflict (LC), our approach remembers the last variables on which search decisions failed. Importantly, the initial ordering behind COS is given by a specified variable ordering heuristic, but contrary to LC, once consumed, this first ordering is forgotten, which makes COS conflict-driven. Our pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Last Conflict [9] (LC) and Conflict Ordering Search [10] (COS) are two variable selectors that tend to branch on the variables that trigger conflicts the most. They can be seen as a plugin that can be combined with another variable selector heuristic.…”
Section: B Black-box Search Heuristicsmentioning
confidence: 99%
“…Last Conflict [9] (LC) and Conflict Ordering Search [10] (COS) are two variable selectors that tend to branch on the variables that trigger conflicts the most. They can be seen as a plugin that can be combined with another variable selector heuristic.…”
Section: B Black-box Search Heuristicsmentioning
confidence: 99%
“…Through this new perspective, we have shown that using the objective as a feature to make decisions can lead to strong results. In addition, further work can be done, for example, with non valued SSs like the ones using a ranking criteria such as COS [5]. Directly applying this work on such SSs is not trivial, and should be a next step.…”
Section: Resultsmentioning
confidence: 99%
“…That is one of the main motivations for the development of black-box constraint solvers, where the only user's concern is to build an efficient model. Blackbox solvers need robust and efficient SSs, and many researches have been done [11,18,5,16,28]. Notably, in Constraint Programming, activity-based search (ABS) [14], impact-based search (IBS) [20] and weighted degrees (Wdeg) [1] are well known stateof-the-art search strategies for combinatorial problems.…”
Section: Introductionmentioning
confidence: 99%
“…The general idea is to perform a certain amount of search, and then if no solution has been found (and unsatisfiability has not been proven), to abandon search and restart from the beginning. Such an approach can only be beneficial if something changes after restarting-in a constraint programming setting, this is usually the variable-ordering heuristic [28,13,29,16]. In this paper, we instead rely upon randomness in our new value-ordering heuristic, and continue to use smallest domain first with static tiebreaking for variable-ordering.…”
Section: Restarting Search and Nogood Recordingmentioning
confidence: 99%